2014
DOI: 10.4315/0362-028x.jfp-14-020
|View full text |Cite
|
Sign up to set email alerts
|

Effective Disinfection of Rough Rice Using Infrared Radiation Heating

Abstract: The objective of this study was to investigate the effect of infrared (IR) heating and tempering treatments on disinfection of Aspergillus flavus in freshly harvested rough rice and storage rice. Rice samples with initial moisture contents (IMCs) of 14.1 to 27.0% (wet basis) were infected with A. flavus spores before the tests. The infected samples were heated by IR radiation to 60°C in less than 1 min, and then samples were tempered at 60°C for 5, 10, 20, 30, 60, or 120 min. High heating rates and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…A. flavus was grown in potato dextrose agar (PDA) (Sigma, St. Louis, MO, USA) at 28 C for 7 days (Kim, Campbell, Mahoney, Chan, & Molyneux, 2004). A conidial suspension of 10 5 cfu/mL was prepared by flooding the culture plates with 0.03% Tween 80 (w/w) (Wang et al, 2014). A volume of 10 ml of the spore suspension was pipetted onto 500 g rough rice in a conical flask, sealed by a double layer aluminum foil, and kept in a 28 C incubator for 14 days until the mold growth was observed.…”
Section: Samplesmentioning
confidence: 99%
“…A. flavus was grown in potato dextrose agar (PDA) (Sigma, St. Louis, MO, USA) at 28 C for 7 days (Kim, Campbell, Mahoney, Chan, & Molyneux, 2004). A conidial suspension of 10 5 cfu/mL was prepared by flooding the culture plates with 0.03% Tween 80 (w/w) (Wang et al, 2014). A volume of 10 ml of the spore suspension was pipetted onto 500 g rough rice in a conical flask, sealed by a double layer aluminum foil, and kept in a 28 C incubator for 14 days until the mold growth was observed.…”
Section: Samplesmentioning
confidence: 99%
“…Wang et al () demonstrated that the energy flux associated with IR heating could result in microbial decontamination in rice with shorter heating duration compared to convective heated air. The authors reported the potential to inactivate A .…”
Section: Introductionmentioning
confidence: 99%
“…flavus molds on rice by using a catalytic IR emitter powered by natural gas. The results by Wang et al () for rice decontamination were based on batch treatments and may not translated to corn drying applications. Compared to rice, corn is less susceptible to stress‐crack formation, and may endure larger doses of IR energy before sensory qualities are compromised.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were incubated for 0, 10, 20, 40, 60, 120 and 240 min. The temperature of 60 °C was chosen based on our previous findings, which confirmed that high drying rate, milling quality and effective disinfections and disinfestation could be achieved at a holding temperature of 60 °C …”
Section: Methodsmentioning
confidence: 99%
“…Much work has been done in our previous research using electromagnetic radiation for rough rice drying. Our reported results demonstrated that rapidly heating rough rice to 60 °C followed by a tempering/holding treatment for several hours can be used as an effective approach to achieve high drying rate and good milling quality . Heretofore, to our best knowledge there are no reports in the literature on decontamination and drying of rough rice using integrated PL and holding treatment.…”
Section: Introductionmentioning
confidence: 92%